2019
DOI: 10.3390/nu11010070
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review of Hydration and Selected Health Outcomes in the General Population

Abstract: Although adequate hydration is essential for health, little attention has been paid to the effects of hydration among the generally healthy population. This narrative review presents the state of the science on the role of hydration in health in the general population, specifically in skin health, neurological function (i.e., cognition, mood, and headache), gastrointestinal and renal functions, and body weight and composition. There is a growing body of evidence that supports the importance of adequate hydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 98 publications
1
68
0
6
Order By: Relevance
“…It leads to an increased feeling of fatigue and reduces mental efficiency by decreasing memory, attention, and response time. It reduces visual and motor coordination being especially important during the learning process [ 7 , 9 , 35 , 36 ]. Fadda et al examined in the RTC study the effect of drinking water on cognitive performance, fatigue, and vigor in school children.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to an increased feeling of fatigue and reduces mental efficiency by decreasing memory, attention, and response time. It reduces visual and motor coordination being especially important during the learning process [ 7 , 9 , 35 , 36 ]. Fadda et al examined in the RTC study the effect of drinking water on cognitive performance, fatigue, and vigor in school children.…”
Section: Discussionmentioning
confidence: 99%
“…Body water was inversely correlated with lymphocyte and directly correlated with platelet-to-lymphocyte ratio. However, little data has been identified in the literature, specifically for these correlations (62)(63)(64)(65)(66)(67)(68)(69), since immune function and hydration has been more assessed in athletes, in response to exercises (67)(68)(69). Specific absolute and lymphocytes subpopulation counting have been assessed in athletes and in patients at high cardiovascular risk, with indirect but inconsistent correlations between lymphocytes and hydration status (70)(71)(72)(73)(74)(75).…”
Section: Linear Correlationsmentioning
confidence: 99%
“…Platelet-to-lymphocyte ratio has been proposed as an inflammatory marker of cardiovascular risk, acute pancreatitis and sarcopenia (76)(77)(78)(79)(80), with some speculations that higher ratio could indicate better hydration status, similarly to the direct linear correlation that we found. This occurs perhaps due to a direct correlation between platelet count and total body water (65,66,81), although this associations remain controversial (64)(65)(66)(67)(68).…”
Section: Linear Correlationsmentioning
confidence: 99%
“…Increased consumption of water has been associated with a reduced risk of obesity, urinary tract infections, chronic kidney disease, cardiovascular disease, and a reduction in the incidence of hyperglycemia [5][6][7][8][9][10][11]. Despite these benefits, recent cross-sectional surveys have shown that 60% of men and 40% of women do not comply with the EFSA recommendations for daily water intake [12], which may alter the long-term health risk profile in persons who habitually consume low volumes of water on a daily basis [13,14]. Although 40% of women were found to not meet current EFSA standards, they were more than twice as likely to meet the adequate intake standards for daily fluid intake than that of men [12].…”
Section: Introductionmentioning
confidence: 99%